PENGARUH RECITATION METHOD TERHADAP HASIL BELAJAR SISWA KELAS VII MTs NEGERI 1 KOTA JAMBI PADA MATA PELAJARAN PPKn - Yahya, Adhisty Yulia; Maulia, Siti Tiara; Salam, M. (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The learning outcomes of seventh grade students at MTs Negeri 1 Jambi City in Citizenship subjects are clearly below the KKM set by the school, which is 75. This is due to the lack of student interest in the learning strategies used in learning citizenship at MTs Negeri 1 Jambi City. Because it does not succeed in captivating students' attention or inspiring them to want to learn more. The purpose of this study was to determine how the resitation approach affects the learning outcomes of seventh grade students at MTS Negeri 1 Jambi City. The type of research used was a pseudo-experiment with a pre-test-post-test-control group design. The research findings show that there is an influence between the resitation method and the learning outcomes of seventh grade students at MTs Negeri 1 Jambi City. This can be proven by the results of the Mann-Whitney test conducted by researchers, namely Zhitung of -2.118 with a Sig value. 0,034. Because the significance level is smaller than 0.05, Ha is accepted and H0 is rejected.